Antihypertensive agents acting on the renin–angiotensin system and the risk of sepsis. (November 2014) - Dial, Sandra; Nessim, Sharon J.; Kezouh, Abbas; Benisty, Jacques; Suissa, Samy
<x xml:space="preserve">Abstract</x> Aims In response to safety concerns from two large randomized controlled trials, we investigated whether the use of telmisartan, an angiotensin receptor blocker (ARB), ARBs as a class and angiotensin‐converting enzyme inhibitors (ACEIs) increase the risk of sepsis, sepsis‐associated mortality and renal failure in hypertensive patients. Methods We performed a nested case–control study from a retrospective cohort of adults with hypertension from the UK General Practice Research Database diagnosed between 1 January 2000 and 30 June 2009. All subjects hospitalized with sepsis during follow‐up were matched for age, sex, practice and duration of follow‐up with 10 control subjects. Exposure was defined as current use of antihypertensive drugs. Results From the cohort of 550 436 hypertensive patients, 1965 were hospitalized with sepsis during follow‐up (rate 6.9 per 10 000 per year), of whom 824 died and 346 developed acute renal failure within 30 days. Compared with use of β‐blockers, calcium‐channel blockers or diuretics, use of ARBs, including telmisartan, was not associated with an elevated risk of sepsis (relative risk 1.09; 95% confidence interval 0.83–1.43); but use ACEIs was (relative risk 1.65; 95% confidence interval 1.42–1.93). Users of ARBs, β‐blockers, calcium‐channel blockers or diuretics, but not users of ACEIs, had lower rates of hospitalization for sepsis compared with untreated hypertensive patients. Findings were similar for sepsis‐related 30 day mortality and renal failure. Conclusions Hypertensive patients treated with ARBs, including telmisartan, do not appear to be at increased risk of sepsis or sepsis‐related 30 day mortality or renal failure. On the contrary, users of ACEIs may have an increased risk.